Effectiveness of Ethylene to Prevent Shriveling Symptoms and Improve Quality of Abiu (Pouteria caimito) Fruit During Storage - Habibi, Irfan; Susanto, Slamet; Hapsari, Dhika Prita; Arif, Abdullah Bin (AGRIVITA Journal of Agricultural Science, 2025)
Abiu fruit harvested at the fully-ripe stage typically exhibits a shorter shelf life compared to those harvested at the half-ripe stage. Despite the longer shelf life, those at the half-ripe stage are more susceptible to shriveling during storage, particularly on the green part. This study aims to mitigate shriveling and enhance the postharvest quality of abiu fruit through ethylene application. The treatments consisted of 2 ethylene application methods (1-second dip and 60-second soak) and 4 concentrations [control (0 ppm), 100, 200, and 400 ppm]. The fruit was stored at room temperature (26 ± 2°C and RH 82 ± 2%) after ethylene application. The results showed that the soak application can reduce shriveling by 31% and extending the shelf life by up to 2 days. Decreasing of shriveling incidence also found in the 100, 200, and 400 ppm ethylene concentration by 29%, 52%, and 52%, respectively which lead to extend the shelf life up to 4 days. The soaking method and 100 ppm ethylene concentration were the most effective among all treatments, which were able to reduce shriveling by up to 63% and extend the shelf life of abiu fruit by up to 4 days.